THE OXIDATION STATE OF EUROPIUM IN HYDROTHERMAL SCHEELITE: IN SITU MEASUREMENT BY XANES SPECTROSCOPY - Brugger J.; Jones H.; Etschmann B.; Chu Y.S.; Vogt S.; Harland C.; Ryan C. (My University, 2006)
X-ray microfluorescence and EuL3 micro-X-ray absorption near-edge structure (XANES) spectroscopy were conducted to determine the distribution and valence state of europium in two samples of scheelite (CaWO4) containing between 40 and 350 ppm Eu. The samples come from hydrothermal gold deposits: the Archean Drysdale deposit in Kalgoorlie, Western Australia (DRY 1) and the Caledonian, intrusion-related Stepnyak deposit in Kazakhstan (USP31). Laser-ablation ICP-MS analyses reveal that both samples are characterized by bell-shape chondrite-normalized REE patterns with a maximum enrichment around Eu, and a small positive or no Eu anomaly. USP31 displays a complex zoning between this pattern and a strongly LREE-enriched pattern with a strong positive Eu-anomaiy. The XANES spectroscopy reveals the coexistence of Eu2+ and Eu3+ in both scheelite samples DRY1 and USP31. The oxidation of Eu in USP31 appears to be inhomogeneous within a single crystal, with zones containing a mixture of Eu2+ and Eu3+ and zones containing more than 90% Eu2+. This study shows that it is possible to obtain semiquantitative element-distribution maps for LREE well as, in optimal conditions, EuL3 XANES spectra on a bending magnet beamline equipped with a solid-state detector.
Keywords: ELEMENTAL MAPPING; EUROPIUM; GOLD DEPOSIT; OXIDATION STATE; RARE-EARTH ELEMENTS; SCHEELITE; X-RAY ABSORPTION NEAR-EDGE SPECTROSCOPY (XANES); Archean; Precambrian::Archean; Докембрий::Архей